Тој мрачен објект на посакувањето. Кон David M. Halperin, What Do Gay Men Want? An Essay on Sex, Risk, and Subjectivity: Ai objekt i errët i dashjes. Për David M. Halperin, What Do Gay Men Want? An Essay on Sex, Risk, and Subjectivity - Dimitrov, Slavčo; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Slavčo Dimitrov | Славчо Димитров Title (Macedonian): Тој мрачен објект на посакувањето. Кон David M. Halperin, What Do Gay Men Want? An Essay on Sex, Risk, and Subjectivity Title (Albanian): Ai objekt i errët i dashjes. Për David M. Halperin, What Do Gay Men Want? An Essay on Sex, Risk, and Subjectivity Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 345-365 Page Count: 20 Citation (Macedonian): Славчо Димитров, „Тој мрачен објект на посакувањето. Кон David M. Halperin, What Do Gay Men Want? An Essay on Sex, Risk, and Subjectivity“, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 345-365. Citation (Albanian): Slavčo Dimitrov, „Ai objekt i errët i dashjes. Për David M. Halperin, What Do Gay Men Want? An Essay on Sex, Risk, and Subjectivity“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 345-365.